Health measurement scales : a practical guide to their development and use / David L. Streiner, Geoffrey R. Norman and John Cairney. - Streiner, David L.; Norman, Geoffrey R.; Cairney, John, 1968- (Oxford medicine online., 2024)
A new edition of this practical guide for clinicians and researchers who wish to develop tools to measure subjective states, attitudes, or non-tangible outcomes in their patients, ideal for those who have no knowledge of statistics.